Comparison of Efficacy (Control of Primary Post-Partum Hemorrhage) after Vaginal Delivery between Balloon Inflation and Uterovaginal Packing - Fatima Rehman, Noor ul Amina, Paras (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the efficacy between balloon inflation and uterovaginal packing in women with primary post-partum hemorrhage. Material and methods: Between April 2021 to October 2021, total 120 patients with PPH after vaginal delivery, having age 18-40 years, both primi or multi paras either booked or un-booked were recruited for this randomized controlled trial. Place of study was Department of Obstetrics & Gynecology, Mardan Medical Complex. Efficacy (control of PPH) after vaginal delivery between balloon inflation and uterovaginal packing was compared. Results: A total of 120 women with PPH were recruited. Mean age was 28.85 ± 5.83 years, in study group A and B mean age was 28.27 ± 5.96 years and 29.43 ± 5.66 years respectively. In study group A, balloon inflation methods was effective among 33 (55%) patients, while in study group B, uterovaginal packing method was successful among 51 (85%) patients for the control of PPH after vaginal delivery. Significantly (P=0.000) higher rate of efficacy was observed in study group B (uterovaginal packing group) as compared to study group A (balloon inflation group). Conclusion: Results of this study showed higher rate of efficacy (control of primary post-partum hemorrhage) in patients of PPH managed with uterovaginal packing as compared to managed with balloon inflation. Most of the patients were multiparas and booked.